TINGKAT PEMANFAATAN FASILITAS DASAR DAN FUNGSIONAL DALAM STRATEGI PENINGKATAN PRODUKSI DI PELABUHAN PERIKANAN PANTAI TEGALSARI KOTA TEGAL JAWA TENGAH - Yahya, Emil; Rosyid, Abdul; Suherman, Agus (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Tegalsari Grade C Fisheries Port expected that it could be growth centre and fishery economic development based on cached fishery, on economic development as a whole. The purpose of this study to know the condition of basic and functional facilities in the Coastal Fishery Port Tegalsari Tegal, analyzing the utilization rate of basic and functional facilities in the Port of Tegal Tegalsari Coastal Fisheries and determine strategies to improve utilization of the basic facilities and functional Tegalsari Grade c Fishing Port City Tegal. This research used descriptive survey method with case study by survey and observation in location. As for collection data is done using observation methods, interviews, secondary data collection, and documentation. Data analyzed by using qualitative and quantitative descriptive method, SWOT analysis used to determine the utilization of port facilities. The results showed that potential of fishery resources in Tegal city reached 23,106,269 kg for a year. Tegalsari Grade c Fishery Port facilities consist of basic facility, functional and supporting facilities generally in good condition. Rate of water ways utilization at 70%, 52.8% of the pool area, 82.5% of deep basin, wharf at 90.6%, 62.69% of the auction office, parking area by 44.33% and twice of total area for existing facilities is area of ports fisheries in PPP Tegalsari. Increasing product’s strategy should be doing with optimization of port facilities that are useful for increasing fish production, improve the type and production value of fishing effort to increase production, maintenance and development of Fishery Port facilities and increasing the number of environmentally fishing gear for economically performance.